1993
DOI: 10.1002/jhet.5570300327
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative cyclization of some aldehyde semicarbazones induced by metallic salts

Abstract: The oxidative cyclization of some aldehyde semicarbazones 10 with four different oxidizing agents has been effected. The structure of the semicarbazones and the nature of cyclizing agent affected the rate and yield of cyclization but they did not show any influence on the regiochemistry of reaction. In fact, 1,2,4‐triazoline 20 was the only heterocyclic ring obtained by the cyclization reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…[19][20][21][22][23] Despite the apparent similarity of these reagents, surprisingly we observed that very different results -both in terms of reaction regiochemistry and yields, and in terms of reaction kinetics -can be achieved by the use of different salts, depending on the hardness/softness of the metal cation (or, more properly, of the solvated metal-counteranion complex), as well as on its intrinsic oxidizing strength. On the grounds of a careful analysis of all available data, we proposed 2a,22,23 (Scheme 2) that the formation of the 1,2,4-triazole ring could be induced by an attack of the oxidizing agent on the tail thioamide-like moiety of the molecule, followed by a single electron transfer (s.e.t.)…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…[19][20][21][22][23] Despite the apparent similarity of these reagents, surprisingly we observed that very different results -both in terms of reaction regiochemistry and yields, and in terms of reaction kinetics -can be achieved by the use of different salts, depending on the hardness/softness of the metal cation (or, more properly, of the solvated metal-counteranion complex), as well as on its intrinsic oxidizing strength. On the grounds of a careful analysis of all available data, we proposed 2a,22,23 (Scheme 2) that the formation of the 1,2,4-triazole ring could be induced by an attack of the oxidizing agent on the tail thioamide-like moiety of the molecule, followed by a single electron transfer (s.e.t.)…”
Section: Introductionmentioning
confidence: 81%
“…Different reagents -such as bromine (or hypobromite), 15,16 bromate or iodate, 17 lead tetraacetate, 18 and high-valent transition metal salts [19][20][21][22][23] -have been used to perform these reactions. The former examples date up to the beginning of the last century; 24 since the pioneer work by Gibson 15 their synthetic and mechanistic aspects have been systematically studied.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6] Several oxidizing agents can be used for the cyclization of semi-and thiosemicarbazones and it has been investigated how the oxidant as well as the structure of the open chain molecules can affect regiochemistry and yield of the process. 1,7-9 2,3,5,6-Tetrachloro-1,4-benzoquinone (CHL-p, 10) and 2,3-dichloro-1,4-naphthoquinone (14) undergo nucleophilic substitution of one or two chlorine atoms by thioacetamide, [10][11][12] thiourea, 13,14 substituted thiourea, 15 thiocarbazones, 16 hydrazine-1,2-dicarbothioamides, 17 thiosemicarbazides, 18 and thiosemicarbazones.…”
Section: Introductionmentioning
confidence: 99%